DAKWAH DAN PROBLEMATIKA STUDI HADIS - Kamarudin, Kamarudin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Hadith is the second source of Islamic law after the   Quran, hich every Moslem should follow it as a guide and   uswah in life and living. On the other hand,  the tradition has its own problems among Mosle!T13, even some of those who opposed its use as a legal law. This issue is a challenge for preachers because the Quran and Sunnah or ljadith are two sources of law are complementary and  mutually explain in easy to understand  and  apply  the  teachings  of  Islam. Therefore,da'wah   should  have  a  strategy  to  reconcile  the good  people of the wrong understanding of tradition as well as the attitude of rejection of /fadith   (opposed Sunnah)  itself so worried will eliminate the use of lfadith in the future.